The physiological basis for exercise and sport - Fox, E.; Bowers, R.; Foss, M. (Brown & Benchmark, 1993)
The longer one remains at altitude, the more performance improves, but it never quite reaches the values that are obtained at sea-level. Acclimatization rate depends upon the individual. There are some who never acclimatize and continue to suffer mountain or altitude sickness while at altitude. Author has a view on the physiology of acclimatization and compares the results of different studies on altitude training in athletes and non-athletes. Implications: 1.Training at altitude might enhance sea-level performance in originally unconditioned, non-athletic individuals. 2.For highly trained athletes, the training intensity required for maintenance of peak performances cannot be achieve at altitude. 3.Altitude training is not a stimulus for further adaptive responses in specific exercises in high-performance athletes.